Gender stereotypes and female exercise behavior: mediating roles of psychological needs and negative emotions - Guo, Kai; Huang, Qian (Frontiers in Psychology, 2025)
IntroductionIntegrating Expectancy-Value Theory, Basic Psychological Needs Theory, and Social Identity Theory, this study aims to examine the impact of gender stereotypes on female exercise behavior and to test the chain mediation effects of psychological needs satisfaction in exercise and negative exercise emotions.MethodsThe study uses adapted scales for gender stereotypes, psychological needs satisfaction in exercise, exercise-related emotions, and exercise behavior to survey 790 women in China.ResultsThe results show that gender stereotypes are significantly negatively associated with female exercise behavior. Both psychological needs satisfaction in exercise and negative exercise emotions mediate the relationship between gender stereotypes and female exercise behavior. Furthermore, psychological needs satisfaction and negative exercise emotions also jointly play a chain mediating role.DiscussionAddressing gender stereotypes and fostering environments that support psychological needs fulfillment could improve women’s engagement in exercise. Future interventions should focus on reducing gender bias in sports and promoting inclusive, supportive exercise environments to enhance women’s participation in physical activity.